Tratamiento de efluentes de lavandería doméstica mediante Opuntia ficus-indica - Llacsahuanga Alfaro, Erika Vanesa (2024)
The coagulant effect of the prickly pear stalk Opuntia ficus-indica in liquefied form was studied, as well as the synergizing effect of alum, as a method of treatment of domestic laundry effluents. An easy-to-use treatment system was installed at home, which consisted of a 250 L storage tank where coagulation was performed and evaluated by the prickly pear liquefaction with a resting time of 48 h, finally followed by a filtration stage with cotton, stone and sand. The purifying effect (coagulation – filtration) of the prickly pear, Opuntia ficus-indica, was initially evaluated with the first wash rinse of 62.5 L, using amounts of 100 g, 200 g, 400 g and 800 g of the liquefied stalk, compared to the control group. The best result of the effluent purification effect was obtained with the use of 200 g of liquefied prickly pear stalk in 62.5 L of domestic laundry effluent. A system for home use with effective biocoagulant was developed for the treatment of domestic laundry effluents, replacing conventional chemical coagulants used in wastewater treatment, providing environmentally friendly technological alternatives that generate fewer pollutants and better water reuse. Regarding the treatment of the final total rinse or complete wash cycle of 250 L, the purifying effect (coagulation –filtration) of the prickly pear, Opuntia ficus-indica, was evaluated, using quantities of 100 g, 200 g, 400 g and 800 g, compared to the control group. The best result of the effluent purification effect was obtained with the use of 200 g of liquefied prickly pear stalk in 250 L of domestic laundry effluent. The synergizing purifying effect (coagulation – filtration) of alum was evaluated, adding Opuntia ficus-indica to the prickly pear treatment, with the first wash rinse of 62.5 L, using quantities of 100 g, 200 g, 400 g and 800 g of the liquefied stalk concentrate, as well as 5625 mg of alum compared to the control group. The best result of the purifying effect of the effluent was obtained with the use of 200 g of prickly pear stalk liquefied with alum in 62.5 L of domestic laundry effluent. The synergizing purifying effect (coagulation – filtration) of the alum was evaluated, in the total rinsing at the end or complete washing cycle of 250 L, the purifying effect (coagulation – filtration) by the prickly pear, Opuntia ficus-indica, using amounts of 100 g, 200 g, 400 g and 800 g, as well as 22500 mg of alum compared to the control group. The best result of the effluent purification effect was obtained with the use of 200 g of prickly pear stalk liquefied with alum in 250 L of domestic laundry effluent. The degree of purification of the treated effluent was evaluated with the analysis of parameters such as COD (chemical oxygen demand), pH, total solids and sulfates. The results were compared with a conventional treatment of the coagulant substance such as ferric chloride.